2013
DOI: 10.3329/bjz.v40i2.14317
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and comparative likelihood of urinary tract infection (UTI) among female out patients in BSMMU

Abstract: Out of 200 urine samples of female out patients from BSMMU hospital, 128 (64%) cases were detected as Escherichia coli positive, 66.67% of cases in summer and 60% in winter. To compare the risks of E. coli infection in summer and winter and also among different age groups, odd ratio (OR) and relative risk (RR) were used as measures of comparative likelihood. The values of both OR and RR were greater than one when the risk of E. coli infection of adults (16-35) was compared with that of middle age (36-50) and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…11 Excessive use of antibiotics, false diagnosis, deficiency of productive research, lack of awareness, and self-medication may cause bacterial resistance due to the development of new genetic variants, resulting from treatment failure either in developed or under developing countries and leading to increased morbidity. 12 , 13 In uropathogenic bacteria, the abundance of virulence genes is coding to different virulence factors, eg FimH: adherence factor produced by uropathogenic Escherichia coli (UPEC) 14 and associated underlying mechanisms making it difficult to treat these infectious diseases. 15 , 16 Bacteria-harboring genetic variants, eg hlyA, Utah, cnf1, ibeA and cdtB in UPEC leading to antibiotic resistance have been increased remarkably and globally become a serious challenge for medical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…11 Excessive use of antibiotics, false diagnosis, deficiency of productive research, lack of awareness, and self-medication may cause bacterial resistance due to the development of new genetic variants, resulting from treatment failure either in developed or under developing countries and leading to increased morbidity. 12 , 13 In uropathogenic bacteria, the abundance of virulence genes is coding to different virulence factors, eg FimH: adherence factor produced by uropathogenic Escherichia coli (UPEC) 14 and associated underlying mechanisms making it difficult to treat these infectious diseases. 15 , 16 Bacteria-harboring genetic variants, eg hlyA, Utah, cnf1, ibeA and cdtB in UPEC leading to antibiotic resistance have been increased remarkably and globally become a serious challenge for medical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The probable cause could be the high temperature in summer season which causes more sweating than in winter, therefore urine production becomes less and concentrated which provides the opportunity for bacterial multiplication. On the contrary, during winter season, less sweating causes more diluted urine production which washes away any multiplying bacteria (Khanum 2013). Simmering et al (2017) found that the seasonal intensity (summer peaks and winter troughs) increased over time among women while decreasing among men.…”
Section: Resultsmentioning
confidence: 99%
“…In Bangladesh it is also one of the most important causes of morbidity at both outdoor and indoor setting. Lack of proper research, faulty diagnostic procedures, abuse of chemotherapeutic agents and little or no preventive measures are all common attributing factors 4 .…”
Section: Introductionmentioning
confidence: 99%